Milroys Disease - The Rarest Cause of Lymphedema - Chowdhury, Faizul Islam; Kabir, Ahmedul; Banik, Jayanta; Paul, Pinaki; Rahman, Matiur; Sarkar, Shohel; Pervez, Shahimur (Journal of Medicine, 2010)
Milroy’s disease is an old term used to describe hereditary congenital lymphedema. It is the rarest of the inherited lymphedema. The cause is a mutation in the VEGFR3 gene and is inherited in an autosomal dominant manner. This gene has been mapped to the telomeric part of the chromosome 5q in the region 5q34-q35. It is characterized by lower limb lymphedema, present at birth or developing soon after. It may be associated with intestinal lymphangiectasia and cholestasis. Here we report a 57 years old male who had been suffering from bilateral leg swelling since birth and finally leveled as a case of Milroy’s disease by positive family history and excluding other causes of lymphedema. We present this case due to the rarity of its occurrence. Keywords: Milroy’s Disease; Lymphedema DOI: 10.3329/jom.v11i2.5471 J MEDICINE 2010; 11 : 189-192